Intervenciones de enfermería en paciente de 27 años con Gangrena Fournier - Delgado Cherres, Roxana Lisbeth (2020)
The application of the Nursing Care Process (ECP) in patients with Fournier gangrene is a central guide that allows the Nursing professional to provide care with methodological support, through the international language NANDA, NOC, NIC. To be successful in the implementation, the development of intellectual, interpersonal and technical competences is required, in addition to the application of reflective practice, which is a strength in the Nursing union. Fournier's gangrene is a perineogenital, polymicrobial necrotizing infectious process, originated by aerobic and anaerobic microorganisms, of rapid evolution, with a poor prognosis. The average age in the present study was similar to the data published by different authors, where urological causes have been more frequent, however in the patient studied in this case it was not possible to determine the main cause.